Ambiente de Treinamento de Acompanhantes de Portadores de Transtorno Espectro Autista em Realidade - Pina Soares, Thiago; Antonio P. de Souza, Marco; B. Marques, Leonardo; C. Monteiro, Dionne (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4184, 2018)
With the technological advancement of the last decade, the use of technology to help and assist in different areas of study, such as medicine, physiotherapy, psychology, etc., is remarkable, since it allows more specific and detailed information for its study, which facilitates the analysis of results. Virtual Reality (VR) is an example of technology that continues to grow in the last decades and has become popular among these areas of study due to its great potential to provide a virtual immersion environment that can simulate any situation and also has the possibility of generate results that can be compared to actual results.